The relationships between the effectiveness of team play and the sporting level of a team - Panfil, R.; Superlak, E. (Human Movement, 2012)
This study aimed at determining what relationships exist between the determinants of team play efficiency (cooperation) for creating scoring situations in volleyball and the sporting level of a team. These relationships take into consideration the number of players who cooperate within a team and the speed at which sets are performed. Methods. The study gathered observational data on how three leading male volleyball teams, namely Brazil, Russia and Serbia, played in the semi-finals of the 2010 World League, finishing first, second and fourth, respectively. The research tool was a self-made data registration sheet which included the description of the chosen variables, namely the type of plays used and how sets were formed, and the criteria for their quantification. The collected results were presented as tables and indexes. An interdisciplinary interpretation of the results was conducted, which included a qualitative identification of the dependencies that existed between the chosen variables. Results. The efficiency of team cooperation when solving situational problems in the offense was not significantly different in the analysed teams. The prevailing activities during the game were those performed in the 2nd tempo, i.e. team play requiring the coordination and synchronization of three players. Players' activity as well as the performance efficiency of the sets they performed in the 2nd tempo increased along with an increase in the sporting efficiency of the examined teams. In the case of sets performed in the 3rd tempo, activity and the efficiency of coordination declined along with the growth of sports efficiency. The suggested indexes of the employment and application of synergy enable us to determine its level within the teams which differ in regards to sports efficiency. A diagnostic value of the index of synergy usage, which is determined by the efficiency of sets in various paces, is higher than a diagnostic value of the index that is determined by the activity of team play. Conclusions. Nowadays, sport teams, especially those which play volleyball at the highest world level, are characterized by a high level of dynamic organization of players' activities, which is manifested in the game with the high efficiency of team play when solving situational problems in the offense, particularly with the use of two or three players conducted in the 1st and 2nd tempos.